159k views
1 vote
Can someone help me I don’t understand this

Can someone help me I don’t understand this-example-1
User XpressGeek
by
5.5k points

2 Answers

3 votes

Answer:

D. -x^2 + 12x + 3.

Explanation:

5x^2 + 9x + 3 - (6x^2 - 3x)

First distribute the negative over the parentheses:

= 5x^2 + 9x + 3 - 6x^2 + 3x

Bring like terms together, then simplify:

= 5x^2 - 6x^2 + 9x + 3x + 3

= -x^2 + 12x + 3.

User Ger Groot
by
5.3k points
2 votes

5x² + 9x + 3 - (6x² - 3x) =

= 5x² + 9x + 3 - 6x²+ 3x =

= (5x² - 6x²) + (9x + 3x) + 3 =

= -x² + 12x + 3

User Phs
by
5.3k points